Modernism and the museum Asian, African, and Pacific art and the London avant-garde - Arrowsmith, Rupert Richard, 1968- (Oxford : Oxford University Press, 2010)
By demonstrating that many of the concepts and styles associated with modernism were actually derived directly from cultures such as Japan, China, Korea, India, Egypt, Assyria, West Africa, and the Pacific Islands, this book provides an entirely new way of looking at the evolution of modernist art and literature in the West.
Includes bibliographical references and index.
Description based on online resource; title from home page (viewed Dec. 16, 2010).
Keywords: Modernism (Art); Modernism (Literature); Museums -- England -- London